Rounding the base: A lower extremity biomechanical analysis in softball players - Schroeder, L. E.; Valenzuela, K. A.; Zhang, S., Orme, J. G.; Weinhandl, J. T. (International Journal of Sports Science & Coaching, 2021)
Contacting the base is a common injury mechanism for base runners in softball, with ankle sprains being the most common type of injury, but it is not known how the base affects lower extremity mechanics. The purpose of this study was to analyze lower extremity biomechanics while rounding a base. Sixteen recreationally active females with previous softball experience completed two base rounding conditions. A base was securely placed on the force place for the with base (WB) condition, and an outline of the base was taped on the force plate for the no base (NB) condition. Three-dimensional right-leg hip, knee, and ankle kinematics and kinetics were measured during the stance phase of the base rounding and analyzed using statistical parametric mapping (SPM). The WB condition resulted in decreased hip abduction (p = 0.034), increased dorsiflexion (p = 0.012), and decreased inversion (p < 0.001) angles. Increased hip extension (p < 0.001) and hip abduction (p = 0.016) moments were exhibited during the WB condition. Decreased hip abduction (p = 0.026), ankle plantarflexor (p < 0.001), and ankle eversion (p < 0.001) moments were also exhibited in the WB condition. The base acts as a lateral banking surface, reducing variables associated with ankle sprains, and likely assists in propelling base runners to the next base without injury.